Simplifying
13 = 2y + -3(y + 4)
Reorder the terms:
13 = 2y + -3(4 + y)
13 = 2y + (4 * -3 + y * -3)
13 = 2y + (-12 + -3y)
Reorder the terms:
13 = -12 + 2y + -3y
Combine like terms: 2y + -3y = -1y
13 = -12 + -1y
Solving
13 = -12 + -1y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add 'y' to each side of the equation.
13 + y = -12 + -1y + y
Combine like terms: -1y + y = 0
13 + y = -12 + 0
13 + y = -12
Add '-13' to each side of the equation.
13 + -13 + y = -12 + -13
Combine like terms: 13 + -13 = 0
0 + y = -12 + -13
y = -12 + -13
Combine like terms: -12 + -13 = -25
y = -25
Simplifying
y = -25